Detection of The Blaz Gene as a Penicillin Resistance Marker in Staphylococcus Aureus From Diabetic Ulcer Swabs - Indrayani, Salsabila Anggia; Pestariati, Pestariati; Astuti, Sri Sulami Endah (Poltekkes Kemenkes Semarang, 2025)
Diabetic ulcer is the most common complication in patients with diabetes mellitus, and Staphylococcus aureus is the predominant bacterial cause of infection. The aim of this study was to detect the presence of the blaZ gene as a penicillin-resistance marker in S. aureus isolated from diabetic ulcer swabs. This research was a descriptive quantitative study. The study population consisted of patients with diabetic ulcers treated at the Diabetes Wound Care Center Branch in Surabaya. Respondents (samples) were selected using purposive sampling, with inclusion criteria being patients diagnosed with diabetic ulcers and eligible for swab collection. A total of 30 ulcer swab samples were obtained between April and May 2025. Isolation and identification were conducted at the Bacteriology Laboratory of Poltekkes Surabaya, resulting in 16 isolates (54%) identified as S. aureus. Among these, 10 isolates (62.5%) were resistant to penicillin G. Detection of the blaZ gene using Real-Time PCR at the Molecular Biology Laboratory of Poltekkes Surabaya showed that 8 isolates (80%) were positive for the gene. These findings indicate that most penicillin-resistant S. aureus isolates carry the blaZ gene, suggesting high potential for β-lactamase production. Future studies are recommended to include larger sample sizes, analyze additional resistance genes, and investigate clinical factors influencing the emergence of antibiotic resistance in diabetic ulcers.